PERKEMBANGAN MORAL DAN AGAMA ANAK USIA DINI GENERASI Z - Kusumawati, Mei Ariani; Yani, Muhammad Turhan; Sya'dullah, Achmad (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This investigation is persuaded by the huge number of cases that happen in children due to the decay in ethics and terrible ethics, so devout instruction must be ingraining and instructed at an early age. The errand of guardians and instructors is exceptionally vital to instruct and instill great ethics so that children have great identities. This inquiry points to portray methodologies for the improvement of devout ethical values in early childhood. In this employment inquiry, the writing thinks about strategy. The information obtained was compiled, analyzed, and concluded that children are the following era of the family and country, who ought to get great instruction so that their potential can be created quickly so that they will develop into human creatures who have solid, able and gifted identities. It is vital for teach and families to play a part and be dependable in giving different sorts of fitting incitement and direction so that the following era will be made with ethics and behavior in agreement with standards.